Early Parenteral Nutrition in Patients with Biliopancreatic Mass Lesions, a Prospective, Randomized Intervention Trial. - Janine Krüger; Peter J Meffert; Lena J Vogt; Simone Gärtner; Antje Steveling; Matthias Kraft; Julia Mayerle; Markus M Lerch; Ali A Aghdassi (PLoS ONE, 2016)
PURPOSE:Patients with biliopancreatic tumors frequently suffer from weight loss and cachexia. The in-hospital work-up to differentiate between benign and malignant biliopancreatic lesions requires repeated pre-interventional fasting periods that can aggravate this problem. We conducted a randomized intervention study to test whether routine in-hospital peripheral intravenous nutrition on fasting days (1000 ml/24 h, 700 kcal) has a beneficial effect on body weight and body composition. MATERIAL AND METHODS:168 patients were screened and 100 enrolled in the trial, all undergoing in-hospital work-up for biliopancreatic mass lesions and randomized to either intravenous nutrition or control. Primary endpoint was weight loss at time of hospital discharge; secondary endpoints were parameters determined by bioelectric impedance analysis and quality of life recorded by the EORTC questionnaire. RESULTS:Within three months prior to hospital admission patients had a median self-reported loss of 4.0 kg (25*th: -10.0 kg and 75*th* percentile: 0.0kg) of body weight. On a multivariate analysis nutritional intervention increased body weight by 1.7 kg (95% CI: 0.204; 3.210, p = 0.027), particularly in patients with malignant lesions (2.7 kg (95% CI: 0.71; 4.76, p < 0.01). CONCLUSIONS:In a hospital setting, patients with suspected biliopancreatic mass lesions stabilized their body weight when receiving parenteral nutrition in fasting periods even when no total parenteral nutrition was required. Analysis showed that this effect was greatest in patients with malignant tumors. Further studies will be necessary to see whether patient outcome is affected as well. TRIAL REGISTRATION:ClinicalTrials.gov NCT02670265.